Makna Teologis Hari Raya Yahudi Dalam Injil Yohanes - Elim Simamora; Dedi Bastanta; Edy Syahputra Tarigan (Jurnal Teologi Cultivation, 2022)
Abstract:Feasts are important in the Jewish tradition. In this study, the writer highlights the theological meaning of the Jewish holidays recorded by the writer of the Gospel of John. The main reason for conducting this study is to see the theological meaning contained in this section and which is considered important for Christians to understand considering that in the history of the development of Christian theology, there is still a connection between OT Judaism and New Testament theology. Easter is a Jewish tradition that is still preserved and celebrated in Christianity, where Easter is closely related to Christ's sacrifice in saving human sins. Through this exegesis study approach, it will be found the depth of the meaning of the Jewish holiday and is associated with theological and practical meanings that can be drawn. In-depth study of the text is indeed a step taken by the author.Abstrak:Hari raya merupakan hal yang penting dalam tradisi Yahudi. Dalam kajian ini penulis menyoroti makna teologis hari raya Yahudi yang dicatat oleh penulis Injil Yohanes. Alasan utama dalam melakukan studi ini adalah untuk melihat makna teologis yang terkandung di dalam bagian ini dan yang dianggap penting untuk dipahami oleh orang-orang Kristen mengingat memang dalam sejarah perkembangan teologi Kristen, tetap saja ada kaitan antara Yudaisme PL dengan teologi Perjanjian Baru. Paskah merupakan tradisi Yahudi yang tetap dipelihara dan dirayakan dalam kekristenan, dimana paskah erat kaitannya dengan korban Kristus dalam menyelamatkan dosa manusia. Melalui pendekatan study eksegesis ini, maka akan didapati kedalaman arti dari hari raya Yahudi tersebut dan dikaitkan dengan makna teologis dan praktis yang bisa ditarik. Studi mendalam atas teks memang merupakan langkah yang diambil oleh penulis.